Capability Of Chromophores - Cellulose Acetatechitosan Membrane Based Colorimetric Sensor For Heavy Metal Detection - Chan, Zi Ying (Universiti Sains Malaysia, 2018)
Simple and fast on-site detection of heavy metals using colorimetric sensor plays an important role in various fields of industry, environment and biological sciences. However, the ability of a colorimetric sensor to induce a distinct color transition highly depends on the optical reagent, for example, type of the chromophore and its detecting conditions such as concentration and pH. In this study, optical reagents such as dithizone (DTZ), pyridylazo naphthol (PAN) and pyridylazo resorcinol (PAR) that responsible to induce color changes were used for Pb2+ detection. DTZ solution at pH4.11 was found to be capable of displaying distinct color transition from dark green to purplish within seconds upon exposed to 0.25ppm Pb2+ (1ppm Pb(NO3)2) due to formation of DTZ-Pb color complex whereas PAN and PAR didn’t provide naked eyes recognition of Pb2+ detection. Therefore, DTZ was used to further construct a stable and sophisticated colorimetric sensor by covalently immobilize DTZ on CA/CS membrane. DTZ at pH 4.11 immobilized on membrane strip had showed the most attracting result in response to Pb2+ in dry sensing condition and without ethanol washing. Besides, the complexation reaction of lead with DTZ has also been explored by FTIR, SEM and UV-vis spectroscopy. Capability of DTZ-CA/CS membrane based colorimetric sensor to detect 0.25ppm Pb2+ (1ppm Pb(NO3)2) had proved its practical application in lead emission monitoring comply with the limit of Environmental Quality (Sewage and Industrial Effluents) Regulations, 1979: Standard B (0.5ppm Pb).